2001
DOI: 10.1021/jp004268o
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Water Molecules and Sodium Ions in Na-Mordenite, by Thermally Stimulated Current Measurement

Abstract: Dielectric relaxation properties of dehydrated and hydrated Na-mordenite are measured by means of thermally stimulated depolarization current (TSDC) spectroscopy. TSDC spectroscopy allows us to determine two characteristic terms which depend on the hydration state: on one hand, the site selectivity of sodium ions and water molecules and on the other hand, the sodium/network interaction energy. Upon hydration, half of the Na+ ions remain embedded in site A, whereas the other Na+ ions are extracted from the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 37 publications
5
34
0
Order By: Relevance
“…They showed that dipolar reorientation is due to Na + , and the TSDC spectrum analysis leads to an assessment of the interaction energies (70-90 kJ/ mol) between the hopped Na + ions and the zeolitic lattice. According to the Na + exchange degree and the nature of the occupied Na + sites, a quantitative and qualitative characterization of each site was given for dehydrated and hydrated Namordenite.The authors [153] determined characteristic terms dependent on (i) the hydration state, (ii) the site selectivity of sodium ions and water molecules, and (iii) the sodium/network interaction energy [154][155][156]. Upon hydration, half of the Na + ions remain embedded in site A, whereas the other Na + ions are extracted from the main channel sites (sites D and E).…”
Section: Natural and Synthetic Amorphous And Crystalline Solidsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that dipolar reorientation is due to Na + , and the TSDC spectrum analysis leads to an assessment of the interaction energies (70-90 kJ/ mol) between the hopped Na + ions and the zeolitic lattice. According to the Na + exchange degree and the nature of the occupied Na + sites, a quantitative and qualitative characterization of each site was given for dehydrated and hydrated Namordenite.The authors [153] determined characteristic terms dependent on (i) the hydration state, (ii) the site selectivity of sodium ions and water molecules, and (iii) the sodium/network interaction energy [154][155][156]. Upon hydration, half of the Na + ions remain embedded in site A, whereas the other Na + ions are extracted from the main channel sites (sites D and E).…”
Section: Natural and Synthetic Amorphous And Crystalline Solidsmentioning
confidence: 99%
“…Finally, it was shown that the interaction energy decreases as the water content increases (from 76 to 42 kJ/mol). This evolution is successfully described using a qualitative model referring to electronegativity and charge-transfer concepts [154][155][156].…”
Section: Natural and Synthetic Amorphous And Crystalline Solidsmentioning
confidence: 99%
“….). Many experimental and theoretical studies have shown that the location of these cations plays a crucial role on the thermodynamics, dynamics, and catalysis of adsorbed molecules (Meunier 2001;Devautour et al 2001;Moïse et al 2001;Maurin et al 2004Maurin et al , 2005Plant et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…So, the presence of adsorbed molecules, interacting directly or indirectly with the cations, can be measured. In previous papers, TSDC was successfully applied to dry and hydrated zeolites [7,8] and clays [9,10] though no quantitative detail about the thermodynamics of the first adsorption stages was extracted from the experimental data.…”
Section: Introductionmentioning
confidence: 99%